(untitled) (Świat Idei i Polityki, 2008)
Poland supported George W. Bush's Iraqi policy and sent soldiers who were supposed to fight, together with Americans, against Saddam Hussein's regime. The decision was highly risky for Poland, as it had been taken at the time when Poland was just about to enter the European Union. Both Germany and France, playing crucial role in the EU, were against any military sanctions towards Iraq. There were predictions that Polish actions, contrary to the European power's vision, would result in a serious crisis. There were even fears that it would impede Poland joining the EU. Indeed, the crisis occurred, however it soon became only the background for European problems. Iraqi issue led also to the deterioration of the relations between Poland and Russia. Moscow's government did not approve of the consolidation of American's position in the Middle-East and in Middle-East Europe.